2012
DOI: 10.1108/13639511211250820
|View full text |Cite
|
Sign up to set email alerts
|

Work characteristics and police officers’ performance

Abstract: PurposeThe purpose of this paper is to examine the effect of work characteristics on members’ self‐efficacy and collective efficacy, and the subsequent effect on police officers’ performance.Design/methodology/approachA multilevel model is adopted to analyze quantitative data obtained by using 812 police officers and 54 chiefs of police stations in Taiwan as the research objects.FindingsThe authors found that work characteristics affected members’ self‐efficacy and collective efficacy, which further affected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…Another interesting phenomenon found by the study is that the study subjects' seniority was negatively associated with their organizational commitment. This and related research (e.g., [74]) have considered that service seniority will affect educational training effectiveness as revealed from related research findings. In other words, senior harbor police officers in Taiwan may have a lower value recognition, effort, and loyalty toward their organizations.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Another interesting phenomenon found by the study is that the study subjects' seniority was negatively associated with their organizational commitment. This and related research (e.g., [74]) have considered that service seniority will affect educational training effectiveness as revealed from related research findings. In other words, senior harbor police officers in Taiwan may have a lower value recognition, effort, and loyalty toward their organizations.…”
Section: Conclusion and Discussionmentioning
confidence: 95%
“…Based on past research [43,74], the factors of gender, age, educational level, and years of service were used as control variables. Empirical studies showed that education may affect the work performance of police officers [75].…”
Section: Control Variablesmentioning
confidence: 99%
“…However, that is not to imply that police self-efficacy has never been examined (see Aremu, 2005; Hsieh et al, 2012; Love & Singer, 1988; Singer & Love, 1987; Taris et al, 2010). Although each of these studies have been important for laying the groundwork for the study of policing and self-efficacy, there are noteworthy limitations future research can expand on.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Second, there is only a small sample of studies that have examined self-efficacy (i.e., perceptions of confidence) in relation to the policing profession. Within them, there is also only scarce discussion of the intricacies of officer experience and how it relates to the development of confidence (Aremu, 2005; Hsieh et al, 2012; Love & Singer, 1988; Singer & Love, 1987). Furthermore, there is yet to be a self-efficacy study conducted with police officers from the United States, despite being the focus of both classic (see Bayley & Bittner, 1984; Brown, 1988; Wilson, 1968) and contemporary (see Willis & Mastrofski, 2014, 2017, 2018) examinations of officer experience and craft.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies have discussed the relationship between organizational innovation and company performance, but few scholars have studied the importance of employees' innovativeness for organizational sustainability. Furthermore, in understanding work design and supporting its improvement, the validated work design questionnaire [13] has proven to be a valuable tool producing benefits in a range of industries, including information technology [30], nursing [31], and policing [32] ( [16], p. 2).…”
Section: Introductionmentioning
confidence: 99%